Adsorptive removal of vinyl polymer tanning agents from aqueous solution using wastewater activated sludge. Issue 24 (20th May 2016) - Zhao, Xia; Ma, Jianzhong; Ma, Hongrui; Gao, Dangge; Lv, Xiangfei; Zhang, Jing
Abstract: Adsorptive studies were carried out on four synthetic vinyl polymer tanning agents removal from aqueous phase onto wastewater activated sludge (AS). Batch experiments investigated the effects of contact time, dosage of adsorbate, extracellular polymeric substances (EPS), coexisted cations, and physical property of sludge flocs on the four vinyl polymers removal by AS to evaluate the kinetics, isotherms, and mechanisms. Almost 96% of polydiallyldimethylammonium chloride-acrylic-acrylamide (PDM-AA-AM), 90% of polydiallyldimethylammonium chloride-acrylic (PDM-AA), 82% of polydiallyldimethylammonium chloride-acrylic-acrylamide-hydroxyethyl acrylate (PDM-AA-AM-HEA), and 56% of polydiallyldimethylammonium chloride (PDM) were removed from aqueous solutions. The kinetics process of adsorption can be described by the pseudo-second-order kinetic equation and the adsorption isotherms fitted to the Langmuir model very well. The adsorption capacity increases with the increase in initial vinyl polymers concentration. Coexisted cations (Ca 2+, Na + ) in aqueous solution restrained vinyl polymers adsorption on AS. The presence of Cr 3+ ions slightly improved the PDM-AA, PDM-AA-AM, and PDM-AA-AM-HEA removal, whereas retarded the PDM removal in some extent. AS are more effective than inactivated sludge in the removal of vinyl polymers. All the four vinyl polymers showed a decrease in the degree of removal when EPS was partial extracted from the biomass. The adsorption mechanisms of AS for vinyl polymers included hydrophobic interaction, surface binding, and electrostatic force. Surface binding may play a major role in PDM-AA, PDM-AA-AM, and PDM-AA-AM-HEA adsorption, while electrostatic interaction may play a major role in PDM removal. This study provided strong evidence that AS can be employed for an effective solution for vinyl polymers syntans removal.